Meta-Analysis: The Effect of Implementing the STEM (Science, Technology, Engineering, Mathematics) Approach on Biology Learning - Wuri Julita; Rahmadhani Fitri; Fitri Arsih (MO.RI Publishing, 2022)
Biology learning is a field of science that requires students to think critically, creatively, and analytically in order to solve problems in each material they study. It is important for students to have the right strategies for learning, and teachers as professionals who teach students must be able to develop effective and efficient learning for students. According to various research, the implementation of STEM (Science, Technology, Engineering, and Mathematics) based learning has a significant impact on students' learning skills. STEM is a suitable alternative for 21st century learning. Through the interconnections of science, technology, engineering, and mathematics, students can solve real-life problems in a systematic manner. The purpose of this article is to analyze the effect of implementing the STEM approach on biology learning. The method used in this article is a literature review method through a review of literature from various sources relevant to the discussion. The results obtained from this article are the influence of the implementation of the STEM approach on biology learning, namely, in improving students' learning outcomes, students' science literacy skills, students' critical thinking skills, students' creativity, and students' scientific thinking skills. Therefore, the application of STEM-based learning can be used as an alternative solution to empower 21st century skills of students, especially in biology learning.